ASSESSING ADMINISTRATIVE EFFECTIVENESS: THE IMPACT OF PERSONALITY TRAITS AND ORGANISATIONAL CLIMATE - Oladimeji, Rasheedat Modupe (Universitas Syiah Kuala, 2024)
The article explores the relationship between personality traits, organisational climate, and administrative effectiveness, focusing on how these factors interact to shape organisational performance. The Five-Factor Model (Big Five) of personality is used to analyse the impact of specific traits on key dimensions of administrative effectiveness, such as efficiency, decision-making quality, and staff satisfaction. Organisational climate plays a significant role in shaping administrative effectiveness, with positive and negative climates fostering high productivity and employee morale. Positive climates, characterised by good communication, lack of support, and managerial incompetence, hinder performance and lead to high turnover rates. The article analyses the impact of organisational climate on various aspects of administrative practice, including employee motivation, communication patterns, and resource allocation. The research also explores the synergistic effects between personality traits and organisational climate, highlighting how individual characteristics can either enhance or mitigate the impact of the organisational environment on administrative effectiveness. The article presents a systematic literature review, synthesis report, and document analysis on the relationship between personality traits, organisational climate, and administrative effectiveness. The review identifies research gaps and highlights the correlation between traits like openness to experience and conscientiousness with effective administrative practices. The article concludes with practical implications for organisations, suggesting using assessment tools to identify personality traits and organisational climate characteristics, implementing training programs to develop individual strengths, and revising organisational policies to create a culture that values diverse personality traits and promotes employee well-being. The article explores the relationship between personality traits, organisational climate, and administrative effectiveness, focusing on how these factors interact to shape organisational performance. The Five-Factor Model (Big Five) of personality is used to analyse the impact of specific traits on key dimensions of administrative effectiveness, such as efficiency, decision-making quality, and staff satisfaction. Organisational climate plays a significant role in shaping administrative effectiveness, with positive and negative climates fostering high productivity and employee morale. Positive climates, characterised by good communication, lack of support, and managerial incompetence, hinder performance and lead to high turnover rates. The article analyses the impact of organisational climate on various aspects of administrative practice, including employee motivation, communication patterns, and resource allocation. The research also explores the synergistic effects between personality traits and organisational climate, highlighting how individual characteristics can either enhance or mitigate the impact of the organisational environment on administrative effectiveness. The article presents a systematic literature review, synthesis report, and document analysis on the relationship between personality traits, organisational climate, and administrative effectiveness. The review identifies research gaps and highlights the correlation between traits like openness to experience and conscientiousness with effective administrative practices. The article concludes with practical implications for organisations, suggesting using assessment tools to identify personality traits and organisational climate characteristics, implementing training programs to develop individual strengths, and revising organisational policies to create a culture that values diverse personality traits and promotes employee well-being.